The Effectiveness Against Traffic Violations with Electronic Traffic Law Enforcement - Yuliantoro, Yuliantoro (International Journal of Law Society Services, 2023)
This study aims to determine and analyze the effectiveness of law enforcement against traffic violations with Electronic Traffic Law Enforcement (ETLE) and to identify and analyze the obstacles in law enforcement against traffic violations with Electronic Traffic Law Enforcement (ETLE) and find out the solutions. This research is an empirical juridical research by combining legal materials (which are secondary data) with primary data obtained in the field. The results of this study indicate that the effectiveness of Electronic Traffic Law Enforcement (ETLE) is still less effective in its implementation, judging from the data on violations that are still occurring, which are increasing compared to before the implementation of the ETLE system. Public awareness of compliance in driving on the road is still lacking and tends to ignore traffic signs because there are no police officers on the road. The factor for the ineffectiveness of implementing Electronic Traffic Law Enforcement (ETLE) is the lack of camera equipment installed on every road and every traffic light so that there is a lack of valid data to detect traffic violators and also there are still many violators found on the highway, especially motorcycle riders who do not drive in an orderly manner in the absence of police officers on duty on the road.